2008
DOI: 10.4103/1319-3767.41743
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of thrombophilic abnormalities during the active state of inflammatory bowel disease

Abstract: Background/Aims:Thromboembolic disease has been recognized as a complication of inflammatory bowel disease (IBD). The relative contributions of inherited or acquired thrombophilia and the inflammatory response to the mechanism of this tendency are unclear. Thrombotic events are more common in active disease although significant numbers also occur spontaneously. The aim of this study was to investigate common thrombophilic markers in patients with active IBD.Methods:Twenty-six patients with IBD who had active d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Numerous studies have been performed in an attempt to detect a relationship with the presence of FVL mutation and the incidence of IBD [ 86 ]. The majority of publications have not found a clear association between FVL and the risk of developing IBD, although FVL continues to be considered a risk factor which may influence the clinical manifestations during IBD [ 84 , 86 88 ]. Similarly, Liang et al [ 89 ] revealed that FVL mutation was not significantly associated with the risk of developing IBD.…”
Section: Factor V Leiden and Inflammation: Infection Sepsis And mentioning
confidence: 99%
“…Numerous studies have been performed in an attempt to detect a relationship with the presence of FVL mutation and the incidence of IBD [ 86 ]. The majority of publications have not found a clear association between FVL and the risk of developing IBD, although FVL continues to be considered a risk factor which may influence the clinical manifestations during IBD [ 84 , 86 88 ]. Similarly, Liang et al [ 89 ] revealed that FVL mutation was not significantly associated with the risk of developing IBD.…”
Section: Factor V Leiden and Inflammation: Infection Sepsis And mentioning
confidence: 99%
“…[ 22 , 23 ] It has been reported that the increased risk of thromboembolism is related to the overexpression of CD40L in PLTs, which may be the only source of CD40L in IBD patients. [ 6 , 24 , 25 ] Patients hospitalized with IBD have a higher risk of VTE and VTE-related mortality compared with hospitalized patients without IBD. [ 26 ] Moderately to severely active UC is an important risk factor for VTE.…”
Section: Discussionmentioning
confidence: 99%
“…The allele frequency of Factor V Leiden mutation was reported to be 4.4% in Europeans and 0.6% in Asia, and was not reported in Africa [45]. Taking into account the differences of races, data from all European countries were further analyzed, excluding two studies from North America [13,33] and one from Egypt [35]. No significant heterogeneity was found in the results of the remaining 16 studies (I 2 = 29.3%, P = 0.13).…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Some studies then suggested the frequency of Factor V Leiden mutation was higher in IBD patients than that in controls, or higher in IBD patients with thrombosis than in those without [13][14][15][16][17][18][19][20][21]. However, some studies found no association between Factor V Leiden mutation and IBD risk [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. One study showed that the mutation was less frequent in thrombotic IBD patients than in thrombotic non-IBD patients [36].…”
Section: Introductionmentioning
confidence: 99%